STUDI TENTANG KEPUTUSAN PEMBELIAN SMARTPHONE PADA KELAS KONSUMEN BARU DI KOTA SEMARANG - Sri Rahayu Tri Astuti (STIE Pelita Nusantara Semarang, 2013)
The purpose of this research is to study about smartphone’s purchase decision at new class costumer at Semarang city. The three independent variables that influence purchase decision are Word of Mouth (WOM), customer value and product quality. Data processing method in this study used a multivariate regression with 75 respondens.